Mutation in protein disulfide isomerase A3 causes neurodevelopmental defects by disturbing endoplasmic reticulum proteostasis. (14th December 2021) - Bilches Medinas, Danilo; Malik, Sajid; Yıldız‐Bölükbaşı, Esra; Borgonovo, Janina; Saaranen, Mirva J; Urra, Hery; Pulgar, Eduardo; Afzal, Muhammad; Contreras, Darwin; Wright, Madison T; Bodaleo, Felipe; Quiroz, Gabriel; et al.
Abstract: Recessive gene mutations underlie many developmental disorders and often lead to disabling neurological problems. Here, we report identification of a homozygous c.170G>A (p.Cys57Tyr or C57Y) mutation in the gene coding for protein disulfide isomerase A3 (PDIA3, also known as ERp57), an enzyme that catalyzes formation of disulfide bonds in the endoplasmic reticulum, to be associated with syndromic intellectual disability. Experiments in zebrafish embryos show that PDIA3 C57Y expression is pathogenic and causes developmental defects such as axonal disorganization as well as skeletal abnormalities. Expression of PDIA3 C57Y in the mouse hippocampus results in impaired synaptic plasticity and memory consolidation. Proteomic and functional analyses reveal that PDIA3 C57Y expression leads to dysregulation of cell adhesion and actin cytoskeleton dynamics, associated with altered integrin biogenesis and reduced neuritogenesis. Biochemical studies show that PDIA3 C57Y has decreased catalytic activity and forms disulfide‐crosslinked aggregates that abnormally interact with chaperones in the endoplasmic reticulum. Thus, rare disease gene variant can provide insight into how perturbations of neuronal proteostasis can affect the function of the nervous system. Synopsis: Dysregulation of endoplasmic reticulum (ER) proteostasis is associated with various neurological problems. Here, study of patients with homozygous mutation in PDIA3 links disturbed proteostasis in intellectual disability directly to effects on neuronal connectivity and function. A homozygous mutation disrupting a redox motif of protein disulfide isomerase A3 (PDIA3) is identified as a possible cause of syndromic intellectual disability. Pathogenic features associated with mutant PDIA3 include reduced enzymatic activity, formation of protein aggregates, and abnormal interaction with ER chaperones. Impaired ER proteostasis due to mutant PDIA3 expression results in altered biogenesis of secretory pathway cargoes including integrins, key adhesion molecules involved in synaptic function and plasticity. Mutant PDIA3 alters neuronal morphogenesis and connectivity, impairing cognitive function such as memory consolidation. Abstract : Study of a rare intellectual disability‐linked variant in ER enzyme PDIA3 links cellular proteostasis defects directly to cytoskeleton and adhesion pathways required for neuronal morphogenesis and connectivity.